Policy of Land Procurement Committee in Determining Validation of Land Fields Between Regulation & Implementation in Toll Road Construction - Mizan, Muhammad Lazuardi Azra; Gunarto, Gunarto (Jurnal Konstatering, 2022)
This study aims to determine and analyze the policy of the land acquisition committee in determining the validation of land parcels in toll road construction. This research method uses a sociological juridical approach with descriptive research specifications. Data sources and data collection methods used primary and secondary data which were analyzed qualitatively. The results of this study indicate that1) The policy regulation of the land acquisition committee in determining the validation of land parcels in toll road construction already has a strong legal basis and also goes through 8 (eight)activity stagesland acquisition for toll road construction. 2) The implementation of the policy of the land acquisition committee in determining the validation of land parcels in toll road construction is good, this can be seen from the number of lands that have been successfully acquired, of the 2,214 plots of land needed there are only 3 plots of land that have a dispute and even then because of a writing error and can be resolved properly through deliberation between the owner of the aggrieved land parcel and the Procurement Committee. Land for road construction. 3) The review of Islamic law regarding the regulation and implementation of the policy of the land acquisition committee in determining the validation of land parcels in the construction of toll roads is already in accordance with the principles of Islamic law, because the land acquisition committee has held deliberations or negotiations with the owner of the land parcel, thereby minimizing the losses faced by the owner. The principle of deliberation is as stated in the Qur'an surah Asy-Shura verse 38, surah Al-Baqarah verse 233 and Surah Ali Imran verse 159.